How conspiracy theorists argue: epistemic capital in the QAnon social media sphere. (3rd July 2022) - Robertson, David G.; Amarasingam, Amarnath
ABSTRACT: What is the role of different epistemic modes in how authority is established in right-leaning conspiratorial narratives? This paper sets out to answer this question through a mixed methods analysis. The first section sets out a model for the analysis of epistemic contestations, using six epistemic modes. This is then applied to a data set of Telegram posts in which key terms are used to identify these epistemic modes. Two questions were then asked of the data. First, how is power related to different kinds of knowledge claims in the far-right conspiratorial milieu? Second, what is the role of these different epistemic modes in how authority is established in right-leaning conspiratorial narratives? How does the epistemology of QAnon influence how they argue? We found that while a broader set of epistemic modes could be identified, there were contestations internally also, particularly around moments of "failed prophecy, " and the role of Christianity and esoteric spiritualities.